A cross-sectional study on knowledge, attitude, and willingness regarding organ donation among students pursuing medical healthcare education in India - Gupta, Aman; Upadhyay, Deepak; Bisht, Mithila; Srivastava, P. C. (International Journal Of Community Medicine And Public Health, 2025)
Background: Organ transplantation is a critical advancement in modern medicine, but a gap exists between organ demand and supply. In India, where awareness and willingness to donate organs remain low, medical students are key stakeholders whose knowledge, attitudes and willingness can significantly influence organ donation rates and public perception. Therefore, the present study was done to assess medical students' knowledge and willingness to donate organs. Methods: The present study was a Cross-sectional study done on 950 students of a private medical college Rohilkhand Medical College and Hospital, Bareilly, Uttar Pradesh, India. Study was done from June 2023 to August 2024. All students from 1st year to final year and interns were included in the study. Results: 52.63% students had partial knowledge of organ donation. Awareness increased with education level, with 90.91% of interns reporting partial or full knowledge. There was high awareness of medical (78.63%) and consent (88.52%) aspects but gaps in legal (37.89% unaware) and ethical (25.16% unaware) considerations were present. 58.42% students were partially agreed with myths related to religious restrictions. Majority (31.60%) were probably willing to donate their body. Key predictors of willingness included awareness of medical (OR=2.1) and legal (OR=1.8) aspects and family history of organ transplantation (OR=2.0). Conclusions: Medical education enhances awareness and willingness regarding organ donation, but gaps in legal and ethical knowledge remain significant. Addressing societal and religious myths through structured educational and sensitization programs is essential among future healthcare professionals.